Dstac is required for normal circadian activity rhythms in Drosophila. - Hsu, I.U.; Linsley, J.W.; Varineau, J.E.; Shafer, O.T.; Kuwada, J.Y. (Chronobiology International, 2018)
The genetic, molecular and neuronal mechanism underlying circadian activity rhythms is well characterized in the brain of Drosophila. The small ventrolateral neurons (s-LNVs) and pigment dispersing factor (PDF) expressed by them are especially important for regulating circadian locomotion. Here we describe a novel gene, Dstac, which is similar to the stac genes found in vertebrates that encode adaptor proteins, which bind and regulate L-type voltage-gated Ca2+ channels (CaChs). We show that Dstac is coexpressed with PDF by the s-LNVs and regulates circadian activity. Furthermore, the L-type CaCh, Dmca1D, appears to be expressed by the s-LNVs. Since vertebrate Stac3 regulates an L-type CaCh we hypothesize that Dstac regulates Dmca1D in s-LNVs and circadian activity.